1999
DOI: 10.1046/j.1365-2141.1999.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

The PNH phenotype cells that emerge in most patients after CAMPATH‐1H therapy are present prior to treatment

Abstract: Paroxysmal nocturnal haemoglobinuria (PNH) cells are deficient in glycosylphosphatidylinositol (GPI) linked antigens due to a somatic mutation of the PIG-A gene in a haemopoietic stem cell. It appears that a PNH clone reaches detectable proportions only when there is selection in its favour. GPI-deficient T lymphocytes have been identified in patients treated with CAMPATH-1H, a monoclonal antibody against the GPI-linked CD52 molecule. CAMPATH-1H selects for cells that are deficient in CD52 (such as PNH-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 15 publications
(20 reference statements)
0
53
1
3
Order By: Relevance
“…Previously published data on T-LGL describe lowered expression of CD52 on the cell surface but not complete absence. 43 In contrast to this report and others on B-cell lymphoma, [39][40][41][42] we demonstrated here that CD52 is decreased in a subset of patients with LGL as a distinct immunophenotypic feature independent of alemtuzumab therapy. Moreover, we found that patients with CD52-negative LGL are refractory to alemtuzumab treatment and that the proportion of deficient cells increases during therapy, likely due to a selection process.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previously published data on T-LGL describe lowered expression of CD52 on the cell surface but not complete absence. 43 In contrast to this report and others on B-cell lymphoma, [39][40][41][42] we demonstrated here that CD52 is decreased in a subset of patients with LGL as a distinct immunophenotypic feature independent of alemtuzumab therapy. Moreover, we found that patients with CD52-negative LGL are refractory to alemtuzumab treatment and that the proportion of deficient cells increases during therapy, likely due to a selection process.…”
Section: Discussioncontrasting
confidence: 54%
“…Based on reports of the emergence of lymphocytes deficient in the expression of GPI-anchored proteins mimicking a PNH phenotype after treatment with alemtuzumab, [39][40][41][42] we investigated whether down-modulated expression of GPI-anchored CD52 may be responsible for the incomplete response rate documented in our LGL patients. Our observation of CD52-negative LGL in the context of alemtuzumab therapy parallels earlier findings in B-cell lymphoma treated with alemtuzumab: decreased membrane expression of CD52 was accompanied by decreased expression of other otherwise constitutively expressed GPI-deficient proteins, including CD55 and CD59.…”
Section: Discussionmentioning
confidence: 99%
“…Similar immunophenotypic changes were described for patients with rheumatoid arthritis and refractory B-NHL including B-CLL receiving alemtuzumab. 30,36,37 PIG-AP-deficient cells were not only observed in T cells and monocytes, 30 but also in granulocytes and erythrocytes which showed diminished expression of CD52. It is hypothesized that alemtuzumab, which targets the PIG-AP CD52, leads to the expansion of a PIG-anchor-deficient cell clone with the phenotypic characteristics of PNH cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in CLL have shown that, in some individuals, there is emergence of a paroxysmal nocturnal hemoglobinuria, CD52 Ϫ clone following treatment with CAMPATH-1H. 20 This clone was probably present at a very low level prior to treatment and is selected out after elimination of CD52 ϩ cells. Another possibility is the acquisition of new somatic mutations in the PIGA gene.…”
Section: Discussionmentioning
confidence: 99%